NURSES’ PERCEPTIONS OF SPIRITUAL CARE - Amal, A.Adriana; Risnah, Risnah; Hidayah, Nur; rifky, muh; yusuf, saldi; Sumarmi, Sumarmi; Mbukwane, Gcinile (Program Studi Ilmu Keperawatan Universitas Jember, 2026)
Background: Holistic nursing care includes spiritual dimensions that are essential to patient well-being. However, spiritual nursing care is still not optimally implemented in daily clinical practice. Many nurses experience challenges in providing spiritual care, such as lack of training, psychological barriers, and minimal institutional support. Objectives: This study aimed to examine nurses' perceptions of spiritual nursing care in inpatient wards at a hospital. Method: This study used a quantitative descriptive design and was conducted at Haji Hospital Makassar. A total of 81 inpatient ward nurses were selected using stratified random sampling. The instrument used was the Indonesian version of the Spiritual Care-Giving Scale (SCGS), which has been validated for validity (CVI > 0.8) and reliability (Cronbach’s Alpha = 0.97). Data analysis was conducted descriptively across five domains of perception: attributes, perspectives, definitions, attitudes, and values in spiritual care. Results: Overall, nurses had a positive perception of spiritual nursing care, with an average total SCGS score of 5.51. The domain with the highest score was “defining spiritual care” (mean = 5.56), reflecting nurses' understanding that spiritual care is an empathetic, culturally sensitive, and patient-centered process. The lowest score was found in the domain of “spiritual service values” (mean = 5.48), indicating that the internalization of broader spiritual values beyond religious practices remains limited. Psychological barriers and conceptual confusion between spirituality and religiosity were also identified. Conclusion: Although nurses recognize the importance of spiritual care, there remains a gap in the internalization of its values and their implementation in clinical practice. Structured training, cultural competency enhancement, and institutional support are needed to improve nurses' readiness and competence in providing meaningful spiritual nursing care. Keywords: spiritual care, nurses’ perceptions, spirituality, professional competence